2022
DOI: 10.3389/fonc.2022.847341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Indocyanine Green Fluorescence Technology in Laparoscopic Radical Gastrectomy

Abstract: BackgroundThis study aimed to observe the application and evaluate the feasibility and safety of indocyanine green (ICG) fluorescence technology in laparoscopic radical gastrectomy (LRG).MethodsPatients who underwent LRG & D2 lymphadenectomy at Qilu Hospital of Shandong University were included between January 2018 and August 2019. According to whether endoscopic injection of ICG was performed, patients were assigned to the ICG group (n=107) and the control group (n=88). The clinicopathologic features,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…14 studies ( 13 , 14 , 17 21 , 23 29 ) reported the operation time and the pooled analysis showed no difference between the ICG and control groups (MD = −9.38, 95% CI = −21.70 to 2.93, P = 0.14) ( Figure 5A ). However, 11 studies ( 13 , 16 21 , 23 , 26 28 ) reported the intraoperative blood loss and showed that the use of ICG could reduce intraoperative blood loss (MD = -17.96, 95% CI = -27.89 to -8.04, P = 0.0004) ( Figure 5B ). 12 studies ( 13 , 14 , 16 21 , 23 , 26 28 ) reported the overall complications and there was a trend that the use of ICG was related to less overall complications with no statistic difference (OR = 0.78, 95% CI = 0.57 to 1.05, P = 0.10) ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…14 studies ( 13 , 14 , 17 21 , 23 29 ) reported the operation time and the pooled analysis showed no difference between the ICG and control groups (MD = −9.38, 95% CI = −21.70 to 2.93, P = 0.14) ( Figure 5A ). However, 11 studies ( 13 , 16 21 , 23 , 26 28 ) reported the intraoperative blood loss and showed that the use of ICG could reduce intraoperative blood loss (MD = -17.96, 95% CI = -27.89 to -8.04, P = 0.0004) ( Figure 5B ). 12 studies ( 13 , 14 , 16 21 , 23 , 26 28 ) reported the overall complications and there was a trend that the use of ICG was related to less overall complications with no statistic difference (OR = 0.78, 95% CI = 0.57 to 1.05, P = 0.10) ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 612 studies were identified, and 17 studies including 15 retrospective studies and 2 randomized controlled trials (RCTs) were ultimately included in this meta-analysis (13,14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The details of the selection procedures are shown to be in line with the PRISMA flowchart (Figure 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some institutions are not possible to use intraoperative endoscopy for LECS in the clinical setting. According to experiences for gastric tumors due to its rarity of duodenal reports, tattooing using dye or blood, preoperative endoscopic clipping (combining with intraoperative portable abdominal radiography, intraoperative laparoscopic ultrasonography or preoperative 3-dimensional CT reconstruction measurements), fluorescence imaging with indocyanine green could be challenging but alterative solutions [ 23 24 25 ]. Compared with these methods, LECS has advantages in easy detection of tumors and direct detection of postanastomotic complications, although it is required need of endoscopic instruments and endoscopists [ 24 ].…”
Section: Discussionmentioning
confidence: 99%